Impediments to Financial Trade: Theory and Applications. (16th September 2019) - Gârleanu, Nicolae; Panageas, Stavros; Yu, Jianfeng
Abstract: We propose a tractable model of an informationally inefficient market featuring nonrevealing prices, general preferences and payoff distributions, but not noise traders. We show the equivalence between our model and a substantially simpler one in which investors face distortionary investment taxes depending on both their identity and the asset class. This equivalence allows us to account for such phenomena as underdiversification. We further employ the model to assess approaches to performance evaluation and find that it provides a theoretical basis for some intuitive practices, such as style analysis, that have been adopted by finance professionals. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.